Seasonal River Chemistry and Lithium Isotopes in the Min Jiang at Eastern Tibetan Plateau: Roles of Silicate Weathering and Hydrology - Liu-Lu, Baiyang; Jin, Zhangdong; Gou, Long-Fei; Zhang, Fei; He, Mao-Yong; Xu, Yang (Frontiers in Earth Science, 2022)
Riverine lithium (Li) isotopes have been considered as a robust tracer for silicate weathering, but processes controlling riverine δ7Li ratios remain controversial. To address the impacts of weathering and hydrology on riverine δ7Li, the seasonal variation of water chemistry in the Min Jiang at the eastern Tibetan Plateau was investigated over December of 2009 to the end of 2010. The results showed distinct seasonal variations in ionic chemistry and δ7Li. Increased river discharge in the monsoon season diluted dissolved ions, and monsoonal hydrological changes caused frequent δ7Li fluctuations. High discharge caused by monsoonal rainfall reduced Li isotope fractionation by shortened rock–fluid interaction time, resulting in lower δ7Li, whereas the input of high δ7Li groundwater and landslide seepage elevated riverine δ7Li, together with lengthened rock–fluid interaction time in less rain intervals. Based on the high-resolution sampling strategy and dataset over one hydrological year, this study highlights that changes of hydrological conditions can have a significant impact on weathering processes and water sources, and therefore on riverine δ7Li variation.